Hazard Mapping-Based Fire Emergency Response Training and its Effect on Workers' Knowledge and Skills at TPS3R Batu City, East Java - Hutagaol, Gery; Sulistyorini, Anita; Supriyadi; Kurniawan, Agung (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Fire is an oxidation process that occurs when three main elements, namely fuel, oxygen, and a heat source, interact, which can cause significant material losses, injuries, and even fatalities. One strategic effort that can be made to minimize its impact is through fire emergency response training, so that workers can handle fires appropriately and effectively. This study aimed to examine the effect of Hazard Mapping-based fire emergency response training on the knowledge and skills of workers at TPS3R in Batu City, East Java. The method used was a quasi-experiment with a pre-test and post-test with a control group design. The research was conducted from October 27, 2025, to November 3, 2025. The sample size of this study consisted of 30 workers, of whom 15 workers from TPS3R Oro-Oro Ombo were assigned to the experimental group, while 15 workers from TPS3R Dadaprejo were assigned to the control group. This study used a questionnaire to measure knowledge and an observation sheet to measure fire emergency response skills among workers. The data were analyzed using the Wilcoxon Signed Rank Test and Mann-Whitney U Test (p < 0.05). The results indicated that the six-day Hazard Mapping-based fire emergency response training intervention had a significant effect on improving the knowledge (p=0.001) and skills (p=0.001) of workers at TPS3R Oro-Oro Ombo in Batu City. Researchers recommend that TPS3R and the Batu City Environmental Agency implement risk control measures through Hazard Mapping and regular occupational safety and health training.